Polyphenylene sulfide composition as well as preparation method and application thereof
By combining crosslinked polyphenylene sulfide with specific oxygen content with silane coupling agent and diatomaceous earth, the conductivity of the carbon layer is reduced and a low-conductive carbon-silicon hybrid structure is formed, which solves the low CTI of the polyphenylene sulfide material The problem is to achieve both high CTI and good mechanical properties.
Patent Information
- Application Number
- CN202411538104.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing polyphenylene sulfide materials have low CTI in high leakage applications, making it difficult to have both high CTI and good toughness. The existing improvement methods have limited effects and will lead to reduced toughness.
The crosslinked polyphenylene sulfide with specific oxygen content is combined with silane coupling agent and diatomaceous earth. By regulating the content and structure of oxygen elements, the formation of carbon layer is reduced, the conductivity is reduced, and the porous structure and miscellaneous diatomaceous earth are passed through the porous structure and complexity of diatomaceous earth. The chemical reaction forms a carbon-silicon hybrid structure with low conductivity, improving CTI and mechanical properties.
The CTI and mechanical properties of the polyphenylene sulfide composition are significantly improved, and have excellent electrical properties and toughness, meeting the needs of high-performance power conversion equipment.
Smart Images

Figure BDA0005112078260000051 
Figure BDA0005112078260000061 
Figure BDA0005112078260000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer compound compositions, and in particular to a polyphenylene sulfide composition and a preparation method and application thereof. Background Art
[0002] Polyphenylene sulfide (PPS) is a high-performance thermoplastic resin, because it has excellent high temperature resistance, corrosion resistance, wear resistance, flame retardancy, high rigidity, low water absorption, and excellent electrical properties, dimensional stability and other properties, and is often used in electronic appliances, automobiles, machinery, chemical industry and other fields. However, although polyphenylene sulfide has excellent heat resistance and flame retardancy, due to its relatively low tracking index (CTI), it is impossible to meet the high leakage application requirements of new energy fields such as solar energy and wind power generation, and high-performance power conversion equipment fields. At present, the existing technology (CN103827213A, CN110791095A, CN112795191A, etc.) is mainly used as a carbonization inhibitor by adding a large amount of metal oxides or hydroxides, and adding components such as polyamide and glass fiber to improve the CTI of polyphenylene sulfide, but the improvement of CTI is limited and the toughness of polyphenylene sulfide will be deteriorated, that is, it is difficult to obtain a polyphenylene sulfide material with both high CTI and good toughness. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a polyphenylene sulfide composition and a preparation method and application thereof.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] In a first aspect, the present invention provides a polyphenylene sulfide composition, comprising the following components, by weight: 85 to 95 parts of polyphenylene sulfide, 5 to 15 parts of a toughening agent, 0.5 to 1.5 parts of a silane coupling agent, and 1 to 3 parts of diatomaceous earth; the polyphenylene sulfide is a cross-linked polyphenylene sulfide containing oxygen elements in the molecular chain, and the mass content of oxygen elements in the polyphenylene sulfide is 0.5% to 6%.
[0006] The present invention uses cross-linked polyphenylene sulfide with a specific oxygen content as a matrix resin, combines it with a silane coupling agent and diatomaceous earth, and uses a toughening agent to form a polyphenylene sulfide composition. By adjusting the content of oxygen in the polyphenylene sulfide, part of the carbon in the polyphenylene sulfide during the carbonization process under the action of current or discharge is promoted to form carbon dioxide with oxygen to reduce the formation of a carbon layer on the surface of the material, and at the same time reduce the regularity of the formed carbon layer, thereby reducing the conductivity of the conductive path of the carbon layer; the silane coupling agent can effectively improve the compatibility of the toughening agent and the polyphenylene sulfide matrix to enhance the bonding force between the two, thereby destroying the formation of a carbon skeleton of the polyphenylene sulfide during the carbonization process; the diatomaceous earth can not only use its rich porous structure to absorb oxygen and react with carbon to generate carbon dioxide during the carbonization process of the polyphenylene sulfide to further reduce carbonization, but also use the silicon, aluminum and other original elements contained in it to hybridize with the carbon layer in the carbonization process of the polyphenylene sulfide to form a carbon-silicon hybrid structure with low conductivity, thereby reducing the formation of the carbon layer and reducing its conductive performance, thereby significantly improving the CTI of the polyphenylene sulfide composition. The cross-linked polyphenylene sulfide can also enhance the entanglement between the cross-linked polyphenylene sulfide and the toughening agent molecular chain, so that the polyphenylene sulfide composition also has excellent mechanical properties.
[0007] In addition, the mass percentage of polyphenylene sulfide in the above-mentioned polyphenylene sulfide composition is preferably ≥80%; the melt mass flow rate of the polyphenylene sulfide at 316°C and 5kg is 50-2000g / 10min according to ISO 1133:2021 standard. The above-mentioned polyphenylene sulfide (cross-linked polyphenylene sulfide containing oxygen elements in the molecular chain) refers to thermal oxygen cross-linked polyphenylene sulfide, which can be obtained by heat-treating linear polyphenylene sulfide in an air atmosphere at 245-255°C, and the mass content of oxygen elements in polyphenylene sulfide can be controlled by adjusting the heat treatment time. The specific surface area of the above-mentioned diatomaceous earth is preferably 20-600m 2 / g, a large proportion of diatomaceous earth in the polyphenylene sulfide composition will lead to poor mechanical properties.
[0008] Optionally, the mass content of oxygen in polyphenylene sulfide can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or 5.5%. The mass content of oxygen in polyphenylene sulfide can be obtained by performing energy spectrum analysis on the material using a scanning electron microscope coupled to energy spectrum (SEM-EDS).
[0009] Optionally, the weight proportion of polyphenylene sulfide in the above-mentioned polyphenylene sulfide composition can be 86 parts, 88 parts, 90 parts, 92 parts, and 94 parts; the weight proportion of the toughening agent can be 6 parts, 8 parts, 10 parts, 12 parts, and 14 parts; the weight proportion of the silane coupling agent can be 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, and 1.4 parts; the weight proportion of diatomaceous earth can be 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, and 2.8 parts.
[0010] As a preferred embodiment of the polyphenylene sulfide composition of the present invention, the mass content of oxygen in the polyphenylene sulfide is 1% to 4%.
[0011] As a preferred embodiment of the polyphenylene sulfide composition of the present invention, the average particle size of the diatomite is 20 to 200 μm; optionally, it can be 25 μm, 50 μm, 75 μm, 100 μm, 125 μm, 150 μm, 175 μm. Studies have found that diatomite within the above average particle size range can not only effectively improve the CTI of the polyphenylene sulfide composition, but also has a significant enhancement effect on the mechanical properties of the polyphenylene sulfide composition. The average particle size of the diatomite can be measured by a microscope.
[0012] As a preferred embodiment of the polyphenylene sulfide composition of the present invention, the silane coupling agent at least includes a silane coupling agent containing an epoxy group.
[0013] The study found that when part or all of the silane coupling agent is a silane coupling agent containing epoxy groups, the epoxy groups in the silane coupling agent can react with the end groups (thiol groups) of polyphenylene sulfide to further destroy the regularity of the carbon skeleton of the polyphenylene sulfide main chain, thereby more effectively reducing the carbon-forming ability of polyphenylene sulfide and thereby improving the CTI of the polyphenylene sulfide composition.
[0014] As a preferred embodiment of the polyphenylene sulfide composition of the present invention, the silane coupling agent containing epoxy groups is coated on the surface of diatomaceous earth.
[0015] The study found that compared with the separate dispersion of silane coupling agent and diatomaceous earth in the polyphenylene sulfide composition, coating the silane coupling agent on the surface of diatomaceous earth is more conducive to improving the dispersion uniformity of diatomaceous earth in the polyphenylene sulfide composition, thereby improving the CTI of the polyphenylene sulfide composition; especially when the silane coupling agent containing epoxy groups is coated on the surface of diatomaceous earth, a large number of epoxy groups in the siloxane coated on the surface of diatomaceous earth can also react with the end groups of different polyphenylene sulfide molecular chains to form a network structure with diatomaceous earth as the cross-linking center, which can not only more effectively destroy the regularity of the carbon skeleton of the polyphenylene sulfide main chain to reduce the carbon-forming ability of polyphenylene sulfide to improve the CTI of the polyphenylene sulfide composition, but also significantly improve the mechanical properties of the polyphenylene sulfide composition.
[0016] As a preferred embodiment of the polyphenylene sulfide composition of the present invention, in the components of the polyphenylene ether composition, the weight proportion of polyphenylene sulfide is 88 to 92 parts, and the weight proportion of the toughening agent is 8 to 12 parts.
[0017] As a preferred embodiment of the polyphenylene sulfide composition of the present invention, the toughening agent includes at least one of a polyolefin elastomer, an ethylene-butyl acrylate-glycidyl methacrylate terpolymer, an ethylene-propylene rubber, a nitrile rubber, a butadiene rubber, an ethylene-vinyl acetate copolymer, a styrene-butadiene-styrene block copolymer, a styrene-ethylene-butylene-styrene block copolymer, a styrene-ethylene-propylene-styrene block copolymer, and maleic anhydride grafts and glycidyl methacrylate grafts thereof.
[0018] As a preferred embodiment of the polyphenylene sulfide composition of the present invention, the silane coupling agent includes at least one of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, methacryloxysilane, propyltrimethoxysilane and 3-aminopropyltrimethoxysilane.
[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned polyphenylene sulfide composition, comprising the following steps: mixing the components evenly and then melt-extruding to obtain the polyphenylene sulfide composition; wherein the melt extrusion can be specifically carried out using a twin-screw extruder, the melt extrusion temperature is 260 to 290°C, and the screw speed of the twin-screw extruder is 100 to 300 rpm.
[0020] In a third aspect, the present invention provides the use of the polyphenylene sulfide composition in the preparation of parts for electronic appliances or electric vehicles.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention uses cross-linked polyphenylene sulfide with a specific oxygen content as a matrix resin, combines it with a silane coupling agent and diatomaceous earth, and adds a toughening agent to form a polyphenylene sulfide composition. The formation of a carbon layer of polyphenylene sulfide under the action of current or discharge is reduced and the conductivity of the carbon layer is reduced, while the degree of entanglement between polyphenylene sulfide and the toughening agent is enhanced, thereby significantly improving the CTI and mechanical properties of the polyphenylene sulfide composition. DETAILED DESCRIPTION
[0023] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0024] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.
[0025] 1. Raw materials and reagents
[0026] 1) Polyphenylene sulfide A: linear PPS, oxygen content of 0%, brand 3450, manufacturer Zhejiang Xinhecheng;
[0027] Polyphenylene sulfide A1 (oxygen content by mass: 0.5%), polyphenylene sulfide A2 (oxygen content by mass: 1%), polyphenylene sulfide A3 (oxygen content by mass: 6%), polyphenylene sulfide A4 (oxygen content by mass: 8%);
[0028] The above-mentioned polyphenylene sulfides A1, A2, A3 and A4 are all thermal oxygen cross-linked PPS, which are obtained by heat treating polyphenylene sulfide A in an air blast oven at 250°C for different times; the mass content of oxygen element in the above-mentioned polyphenylene sulfide is obtained by energy spectrum analysis of the material using scanning electron microscopy coupled to energy spectrum (SEM-EDS).
[0029] 2) Toughener 1: ethylene-butyl acrylate-glycidyl methacrylate terpolymer, brand name PTW, manufacturer: Dow Chemical, USA;
[0030] Toughener 2: Maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, brand FG1901, manufacturer: Kraton, USA.
[0031] 3) Silane coupling agent 1: γ-glycidyloxypropyltrimethoxysilane, brand Z-6040, manufactured by Dow Corning, USA;
[0032] Silane coupling agent 2: γ-aminopropyltriethoxysilane, brand name Z-6011, manufactured by Dow Corning, USA;
[0033] Titanate coupling agent: isopropyl tri(dioctylphosphoyl) titanate, brand KR-12, manufactured by Kenrich, USA.
[0034] 4) Diatomaceous earth 1, diatomaceous earth 2 and diatomaceous earth 3 were obtained by crushing and sieving large-particle diatomaceous earth (brand name Celite R566, manufacturer French Inge Ceramics), wherein the average particle size of diatomaceous earth 1 was 25 μm, the average particle size of diatomaceous earth 2 was 85 μm, and the average particle size of diatomaceous earth 3 was 200 μm.
[0035] Activated carbon, brand GH-20, manufactured by Jiangsu Enkai Activated Carbon Co., Ltd.;
[0036] Carbonization inhibitor 1 is magnesium hydroxide, and carbonization inhibitor 2 is triphenyl phosphate, both of which are commercially available.
[0037] 2. Examples 1 to 13 and Comparative Examples 1 to 7
[0038] Table 1 Weight percentage of each component of the polyphenylene ether composition in Examples 1 to 12
[0039]
[0040] The preparation method of the polyphenylene sulfide composition in Examples 1 to 4 and Examples 7 to 12 comprises the following steps: firstly mixing the silane coupling agent 1 with diatomaceous earth according to the formula to form diatomaceous earth coated with the silane coupling agent 1, then uniformly mixing the diatomaceous earth with the polyphenylene sulfide and the toughening agent, and then adding the mixture to a twin-screw extruder for melt extrusion to obtain the polyphenylene sulfide composition; wherein the rotation speed of the twin-screw extruder is 400 rpm, the feeding rate is 450 kg / h, and the extrusion temperature is 280°C.
[0041] The preparation method of the polyphenylene sulfide composition in Example 5 comprises the following steps: firstly mixing the silane coupling agent 1 with diatomaceous earth according to the formula to form diatomaceous earth coated with the silane coupling agent 1, then uniformly mixing the diatomaceous earth with the polyphenylene sulfide, the toughening agent and the silane coupling agent 2, and then adding the mixture to a twin-screw extruder for melt extrusion to obtain the polyphenylene sulfide composition; wherein the rotation speed of the twin-screw extruder is 400 rpm, the feeding rate is 450 kg / h, and the extrusion temperature is 280°C.
[0042] The preparation method of the polyphenylene sulfide composition in Example 6 comprises the following steps: directly mixing polyphenylene sulfide, toughening agent, silane coupling agent 2 and diatomaceous earth according to the formula and then adding them into a twin-screw extruder for melt extrusion to obtain the polyphenylene sulfide composition; wherein the rotation speed of the twin-screw extruder is 400 rpm, the feeding rate is 450 kg / h, and the extrusion temperature is 280°C.
[0043] Example 13
[0044] An embodiment of the polyphenylene sulfide composition of the present invention, the polyphenylene sulfide composition of this embodiment is basically the same as that of embodiment 1, except that the preparation method of the polyphenylene sulfide composition comprises the following steps:
[0045] According to the formula, polyphenylene sulfide A1, toughening agent 1, silane coupling agent 1 and diatomaceous earth 1 are directly mixed evenly and added into a twin-screw extruder for melt extrusion to obtain a polyphenylene sulfide composition; wherein the rotation speed of the twin-screw extruder is 400 rpm, the feeding rate is 450 kg / h, and the extrusion temperature is 280°C.
[0046] Table 2 Weight parts of each component of the polyphenylene sulfide composition in Comparative Examples 1 to 7
[0047]
[0048] The preparation method of the polyphenylene sulfide composition in Comparative Examples 1 to 7 comprises the following steps: directly mixing the components evenly according to the formula and then adding them into a twin-screw extruder for melt extrusion to obtain the polyphenylene sulfide composition; wherein the rotation speed of the twin-screw extruder is 400 rpm, the feeding rate is 450 kg / h, and the extrusion temperature is 280°C.
[0049] 3. Performance testing
[0050] 1) Tensile strength: tested according to standard ISO 527-1-2021, with a tensile rate of 50 mm / min.
[0051] 2) Izod notched impact strength: tested in accordance with standard ISO 180:2019, type A notch.
[0052] 3) CTI test: According to IEC 60112:2020 standard, the highest voltage at which the test material can pass 50 drops of electrolyte without failure.
[0053] Table 3 Properties of the polyphenylene sulfide compositions in various embodiments and comparative examples
[0054]
[0055] According to the data in Table 3, the CTI of the polyphenylene sulfide compositions in Examples 1 to 13 reaches 200 to 210 V, and the Izod notched impact strength is greater than or equal to 16 kJ / m 2 , and the tensile strength reaches 45-55MPa, indicating that the polyphenylene sulfide composition of the present invention has both excellent CTI and good mechanical properties. At the same time, according to Comparative Examples 1 and 2, it can be seen that the mass content of oxygen elements in polyphenylene sulfide is too low or too high, which cannot balance the CTI and toughness of the polyphenylene sulfide composition, resulting in poor CTI or toughness and difficult to meet application requirements; according to Example 13 and Comparative Example 3, it can be found that compared with the silane coupling agent containing epoxy groups, the titanate coupling agent cannot react with the end group (thiol group) of polyphenylene sulfide, nor can it hybridize with the carbon layer in the carbonization process of polyphenylene sulfide to form a carbon-silicon hybrid structure with low conductivity, resulting in poor CTI of the polyphenylene sulfide composition, and at the same time, it will also reduce the toughness of the polyphenylene sulfide composition to a certain extent. In addition, according to Comparative Examples 4 and 5, it can be seen that although the use of a carbonization inhibitor can also make the polyphenylene sulfide composition maintain good toughness, it is difficult to effectively improve the CTI of the polyphenylene sulfide composition. According to Comparative Examples 6 and 7, it can be found that replacing diatomaceous earth with activated carbon has similar performance to that without adding porous materials, and it is difficult to effectively improve the CTI of the polyphenylene sulfide composition.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polyphenylene sulfide composition, characterized in that: By weight, it includes the following components: 85-95 parts of polyphenylene sulfide, 5-15 parts of toughening agent, 0.5-1.5 parts of silane coupling agent and 1-3 parts of diatomaceous earth; the polyphenylene sulfide is a cross-linked polyphenylene sulfide containing oxygen elements in the molecular chain, and the mass content of oxygen elements in the polyphenylene sulfide is 0.5%-6%.
2. The polyphenylene sulfide composition according to claim 1, characterized in that The mass content of oxygen element in the polyphenylene sulfide is 1% to 4%.
3. The polyphenylene sulfide composition according to claim 1, characterized in that The average particle size of the diatomaceous earth is 20 to 200 μm.
4. The polyphenylene sulfide composition according to claim 1, characterized in that The silane coupling agent at least includes a silane coupling agent containing an epoxy group.
5. The polyphenylene sulfide composition according to claim 4, characterized in that The silane coupling agent containing epoxy groups is coated on the surface of diatomaceous earth.
6. The polyphenylene sulfide composition according to claim 1, characterized in that Among the components of the polyphenylene ether composition, the weight proportion of polyphenylene sulfide is 88 to 92 parts, and the weight proportion of the toughening agent is 8 to 12 parts.
7. The polyphenylene sulfide composition according to any one of claims 1 to 6, characterized in that The toughening agent includes at least one of polyolefin elastomer, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, ethylene-propylene rubber, nitrile rubber, butadiene rubber, ethylene-vinyl acetate copolymer, styrene-butadiene-styrene block copolymer, styrene-ethylene-butylene-styrene block copolymer, styrene-ethylene-propylene-styrene block copolymer and their maleic anhydride grafts and glycidyl methacrylate grafts.
8. The polyphenylene sulfide composition according to claim 1, characterized in that The silane coupling agent includes at least one of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, methacryloxypropyltrimethoxysilane and 3-aminopropyltrimethoxysilane.
9. The method for preparing the polyphenylene sulfide composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly and then melting and extruding the components to obtain a polyphenylene sulfide composition.
10. Use of the polyphenylene sulfide composition according to any one of claims 1 to 8 in the preparation of parts for electronic appliances or electric vehicles.
Citation Information
Patent Citations
Polyphenylene sulfide resin composition, method for producing same, and molded product of same
CN103827213A
Polyphenylene sulfide composite material, preparation method and applications thereof
CN110791095A
High-CTI polyphenylene sulfide composite material and preparation method thereof
CN112795191A
Ablation-resistant polyphenyl ether composition and preparation method thereof
CN115594970A
PA / PPE composite material and preparation method and application thereof
CN117700985A
